(untitled) (Web of Teachers: Inderscience Research, 2024)
And the specific image of the nation is largely shaped by folk pedagogy. The identity of a people, a nation is manifested, first of all, in its customs, rituals, ceremonies, etiquette, customs and traditions are essentially manifestations of folk pedagogy. The study of problems related to Uzbek folk pedagogy is also essential for the theory and practice of pedagogy.